Influence of injector hole number on the performance and emissions of a DI diesel engine fueled with biodiesel-diesel fuel blends - SAYIN, CENK; GÜMÜŞ, METİN (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
In diesel engines, fuel atomization process strongly affects the combustion and emissions. Injector hole number (INHN) particular influence on the performance and emissions because both parameters take important influence on the spray parameters like droplet size and penetration length and thus on the combustion process. Therefore, the INHN effects on the performance and emissions of a diesel engine using biodiesel and its blends were experimentally investigated by running the engine at four different engine loads in terms of brake mean effective pressure (BMEP) (12.5, 25, 37.5 and, 50 kPa). The injector nozzle hole size and number included 340 x 2 (340 mu m diameter holes with 2 holes in the nozzle), 240 x 4, 200 x 6, and 170 x 8. The results verified that the brake specific fuel consumption (BSFC), carbon dioxide (CO2) and nitrogen oxides (NOx) emission increased, smoke opacity (SO), hydrocarbon (HC) and carbon monoxide (CO) emissions reduced due to the fuel properties and combustion characteristics of biodiesel. However, the increased INHN caused a decrease in BSFC at the use of high percentage biodiesel diesel blends (B50 and B100), SO and the emissions of CO, HC. The emissions of CO2 and NOx increased. Compared to the original (ORG) INHN, changing the INHN caused an increase in BSFC values for diesel fuel and low percentage biodiesel-diesel blends (B5 and B20). (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Injector hole number and size; Biodiesel; Emissions; Diesel engine; COMBUSTION CHARACTERISTICS; UNREGULATED EMISSIONS; EXHAUST EMISSIONS; PALM OIL; FLOW